2020
DOI: 10.18632/oncotarget.27732
|View full text |Cite
|
Sign up to set email alerts
|

Novel combination therapy for melanoma induces apoptosis via a gap junction positive feedback mechanism

Abstract: Metastatic melanoma cells overexpressing gap junctions were assayed for their ability to propagate cell death by a novel combination therapy that generates reactive oxygen species (ROS) by both 1) non-thermal plasma (NTP) and 2) tirapazamine (TPZ) under hypoxic conditions. Results demonstrate additive-to-synergistic effects of combination therapy compared to each agent individually. NTP induces highly localized cell death in target areas whereas TPZ partially reduces viability over the total surface area. Howe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(13 citation statements)
references
References 44 publications
2
11
0
Order By: Relevance
“…While monotherapy with tirapazamine, a DNA-damaging compound, failed to elicit a significant anticancer response, promising results were obtained using combination therapy with NTP (non-thermal plasma), also called ‘cold plasma’ ( Table 1 ). NTP alone strongly induced ROS production and subsequent apoptotic response, whereas together with tirapazamine it displayed even higher effectiveness, resulting in 90% reduction in tumor volume in a murine melanoma model [ 142 ]. Another hypoxia-activated prodrug with DNA-alkylating activity, TH-302, also reduced tumor volume in combination with a standard chemotherapeutic (temozolimide) or inhibitor of multiple receptor tyrosine kinases (sunitinib), especially, when melanoma cells were first pre-treated with hypoxia-targeting drug ( Table 1 ) [ 143 , 149 ].…”
Section: Hypoxiamentioning
confidence: 99%
“…While monotherapy with tirapazamine, a DNA-damaging compound, failed to elicit a significant anticancer response, promising results were obtained using combination therapy with NTP (non-thermal plasma), also called ‘cold plasma’ ( Table 1 ). NTP alone strongly induced ROS production and subsequent apoptotic response, whereas together with tirapazamine it displayed even higher effectiveness, resulting in 90% reduction in tumor volume in a murine melanoma model [ 142 ]. Another hypoxia-activated prodrug with DNA-alkylating activity, TH-302, also reduced tumor volume in combination with a standard chemotherapeutic (temozolimide) or inhibitor of multiple receptor tyrosine kinases (sunitinib), especially, when melanoma cells were first pre-treated with hypoxia-targeting drug ( Table 1 ) [ 143 , 149 ].…”
Section: Hypoxiamentioning
confidence: 99%
“…Bagati et al reported additive-to-synergistic effects of a NTP combination therapy with the DNA-damaging agent tirapazamine in in vitro and in vivo metastatic melanoma cells, which underline the potential of NTP to improve cancer therapy via GJ modulation [ 163 ]. The authors observed that when high Cx26-GJs expression was induced in these cells, the combinatorial effects of NTP + tirapazamine therapy was augmented, spreading cell death.…”
Section: Oxidative Stress On Gjs As a Cancer Therapeutic Strategymentioning
confidence: 99%
“…The authors observed that when high Cx26-GJs expression was induced in these cells, the combinatorial effects of NTP + tirapazamine therapy was augmented, spreading cell death. The presence of Cx26-GJs facilitated RONS cell penetration and signaling, while increased Cx26 protein expression and amplified tumoricidal activity [ 163 ]. Furthermore, they also observed an immune response through differential regulation of cytokines and chemokines, suggesting potential for this therapy to induce a cytotoxic immune response [ 163 ].…”
Section: Oxidative Stress On Gjs As a Cancer Therapeutic Strategymentioning
confidence: 99%
See 1 more Smart Citation
“…ROS production via NTP has a selectively cytotoxic effect within melanoma as compared to normal keratinocytes in vitro [ 19 ]. NTP has been demonstrated to have a cytotoxic effect on cancer cells from in vitro and in vivo experiments [ 20 , 21 , 22 , 23 ]. More recently, NTP has been utilized in phase I clinical trials which showed successful parameters for safety following surgical resection in solid tumors [ 24 ].…”
Section: Introductionmentioning
confidence: 99%